Optical and structural studies of phase transformations and composition fluctuations at annealing of Zn₁₋xCdxO films grown by dc magnetron sputtering - Kolomys, O.; Romanyuk, A.; Strelchuk, V.; Lashkarev, G.; Khyzhun, O.; Timofeeva, I.; Lazorenko, V.; Khomyak, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Ternary Zn₁₋xCdxO (x < 0.12) alloy crystalline films with highly preferred orientation (002) have been successfully deposited on sapphire c-Al₂O₃ substrates using the direct current (dc) reactive magnetron sputtering technique and annealed at temperature 600 °C in air. The structural and optical properties of Zn₁₋xCdxO thin films were systematically studied using X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), micro-Raman and photoluminescent (PL) spectroscopy. XPS measurements clearly confirmed Cd incorporation into ZnO lattice. XRD data revealed that the growth of wurtzite Zn₁₋xCdxO films occurs preferentially in the (002) direction. Also, when the Cd content is increased, the XRD peaks shift towards smaller angles and the full width at half-maximum of the lines increases. When the Cd content increases, LO A1 ( Zn₁₋CdxO )-like Raman modes show composition dependent frequency decrease and asymmetrical broadening. The near band-edge PL emission at room temperature shifts gradually to lower energies as the Cd content increases and reaches 2.68 eV for the highest Cd content (x = 0.12). The analysis of NBE band emission and Raman LO A1 ( Zn₁₋xCdxO ) mode shows that at a higher Cd content the coexistence of Zn₁₋xCdxO areas with different concentrations of Cd inside the same film occurs. The presence of CdO in annealed Zn₁₋xCdxO films with the higher Cd content was confirmed by Raman spectra of cubic CdO nanoinclusions. The XRD data also revealed phase segregation of cubic CdO in annealed Zn₁₋xCdxO films (Tann = 600 °C) for x ≥ 0.013.